Amyloid-beta and tau protein beyond Alzheimer’s disease - Morteza Abyadeh; Vivek Gupta; Joao A Paulo; Arezoo Gohari Mahmoudabad; Sina Shadfar; Shahab Mirshahvaladi; Veer Gupta; Christine T O. Nguyen; David I Finkelstein; Yuyi You; Paul A Haynes; Ghasem H Salekdeh; et al. (Neural Regeneration Research, 2024)
The aggregation of amyloid-beta peptide and tau protein dysregulation are implicated to play key roles in Alzheimer’s disease pathogenesis and are considered the main pathological hallmarks of this devastating disease. Physiologically, these two proteins are produced and expressed within the normal human body. However, under pathological conditions, abnormal expression, post-translational modifications, conformational changes, and truncation can make these proteins prone to aggregation, triggering specific disease-related cascades. Recent studies have indicated associations between aberrant behavior of amyloid-beta and tau proteins and various neurological diseases, such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis, as well as retinal neurodegenerative diseases like Glaucoma and age-related macular degeneration. Additionally, these proteins have been linked to cardiovascular disease, cancer, traumatic brain injury, and diabetes, which are all leading causes of morbidity and mortality. In this comprehensive review, we provide an overview of the connections between amyloid-beta and tau proteins and a spectrum of disorders.